Applying a gender lens to biodiversity conservation in High Asia - Alexander, Justine Shanti; Murali, Ranjini; Mijiddorj, Tserennadmid Nadia; Agvaantseren, Bayarjargal; Lhamo, Chemi; Sharma, Deepshikha; Suryawanshi, Kulbhushansingh Ramesh; Zhi, Lu; Sharma, Koustubh; Young, Juliette Claire (Frontiers in Conservation Science, 2023)
Community-based conservation efforts represent an important approach to facilitate the coexistence of people and wildlife. A concern, however, is that these efforts build on existing community structures and social norms, which are commonly dominated by men. Some biodiversity conservation approaches may consequently neglect women’s voices and deepen existing inequalities and inequities. This paper presents two community case studies that draw upon the knowledge and experience gained in our snow leopard conservation practice in two pastoral and agro-pastoral settings in Mongolia and India to better understand women’s roles and responsibilities. In these settings, roles and responsibilities in livestock management and agriculture are strongly differentiated along gender lines and significant gaps remain in women’s decision-making power about natural resources at the community level. We argue that context-specific and gender-responsive approaches are needed to build community support for conservation actions and leverage women’s potential contributions to conservation outcomes.